Unshadowing of Economic Processes in Ukraine – is the Main Condition for the Development of Entrepreneurship (Economics and region, 2021)
The article is devoted to the topical issue of unshadowing of economic processes in Ukraine. The analysis of the level of the shadow economy in Ukraine is carried out, the dynamics of this indicator is characterized. The essence of the main ways of the mechanism of unshadowing of the Ukrainian economy is revealed. The monitoring of the ratings of the countries of the world was carried out, the place of Ukraine was determined in them. The results indicate unfavorable conditions for the development of entrepreneurship in Ukraine. The main measures for unshadowing the national economy are proposed. The article notes the importance of the digitalization of economic processes as one of the directions of the unshadowing of Ukrainian economy.
Keywords: unshadowing; shadow economy; level of shadowing; GDP; entrepreneurship; rating; digitalization